ANALISIS PENGENDALIAN INTERN PERSEDIAAN BARANG DAGANG DAN PENERAPAN AKUNTANSI PADA PT. INDAHWATI SARI - Luh Gede Kusuma Dewi; Ni Luh Putu Sandrya Dewi; Putu Ayu Kris Diantari Putri (Jurnal Widya Akuntansi dan Keuangan, 2020)
Problems that often occur in companies is that inventory management must be optimal. Inventory is a very large company asset. So, control and application is very important. Therefore, internal control system must be implemented and carried out properly and effectively in order to avoid such mistakes or fraud. The purpose of this study was to determine the internal control of merchandise inventory and the application of its accounting at PT. Indahwati Sari. The method used is perpetual recording system. The valuation method used is FIFO, and Financial Accounting Standards (PSAK) NO.14 regarding inventory. The results are inventory internal control system at PT. Indahwati Sari is running quite effectively.